Intrinsic Rivalry. Can White Bears Help Us With the Other Side of Consciousness? - Havlík, Marek; Kozáková, Eva; Horáček, Jiří (Frontiers in Psychology, 2019)
Studies of consciousness have traditionally been based mainly upon the perceptual domains of consciousness. However, there is another side of consciousness, represented by various types of intrinsic conscious experiences. Even though intrinsic experiences can represent up to 50 percent of our conscious experiences, they are still largely neglected in conscious studies. We assume there are two reasons for this. Firstly, the field of intrinsic conscious experiences is methodologically far more problematic than any other. Secondly, specific paradigms for capturing the correlates of intrinsic conscious experiences are almost non-existent. Nevertheless, we expect the intrinsic side of consciousness to soon take its place in conscious studies, but first new experimental paradigms will have to be devised, which would be of a similar design to the paradigms used in studies of perceptual consciousness. In this hypothesis and theory article, we propose such a hypothetical paradigm, present the exploratory data of our proof-of-concept study, discuss its use, and address its shortcomings and their possible remediation.